Penguatan UMKM Tuah Negeri Melalui Inovasi Produksi Batu Bata Dan Kelompok Usaha Keripik Singkong Berbasis Pemberdayaan Perempuan Dan Digitalisasi - Arafat, Lathif; Meta, Williya; Hamdi, Raspan; Sihombing, Aland Polma Naek; Belva, Tatia Patricia; Maherlido, Sintia; Septianda, Mhd. Ega; Alicia, Winda Gokma Uli; Azqi, N. Muhammad (LPPM UMRI, 2026)
Tuah Negeri Village, located in Tenayan Raya District, Pekanbaru City, is dominated by low-income communities working in informal sectors such as brickmaking and home-based microenterprises. The 2025 “BEM Berdampak” Community Service Program aims to enhance local economic capacity through the application of appropriate technology and managerial training. The methods include socialization, technical and managerial training, technology implementation, mentoring, and evaluation. The results show a significant improvement: brick production increased from 1,500–2,000 to 10,000 pieces per day, and cassava chips production rose from 5 kg to 25 kg per week. The partners also developed simple financial recording and digital marketing skills. This program successfully improved entrepreneurial competence, production efficiency, and women’s economic participation while supporting SDGs goals 1 (No Poverty), 5 (Gender Equality), and 8 (Decent Work and Economic Growth). Keywords: Community empowerment, appropriate technology, MSMEs, Tuah Negeri, SDGs.